Die opleiding van ingenieurs-in-opleiding in Yskor se Mynboudepartement - deur B. C. Alberts (The Southern African Institute of Mining and Metallurgy, 1987)
Graduate engineers are a scarce and valuable resource. The situation is aggravated by the 2 years of national service, resulting in the elapse of 6 years after matriculation before a young engineer can start his practical training. After having started work, it is therefore imperative that employees in this category should be trained as effectively as possible in (1) the specialized activities of the employer and (2)the employer's specific work practices. Knowledge and experience of these two areas are vitally important for productive work performance by young engineers. Consequently, it is Iscor's primary objective to enable young graduates, in this case engineers, to obtain the knowledge and experience necessary for productive work in the shortest possible time. Iscor's training programme is therefore structured to enable the young engineer to - perform high-level engineering work and to make sound engineering decisions as soon as possible, - gain a thorough background of the employer's production processes, plant, and equipment, - become thoroughly acquainted with Iscor's work practices, policies, and procedures, - acquire a sound knowledge of Iscor's management techniques and philosophies, - do productive work during the training period, - obtain the following additional qualifications as soon as possible: . Government certificate of competency (legally required before appointment to certain positions) . registration as a professional engineer. Iscor's training programmes are no longer based on predetermined periods of time for each department and work practice. Neither is it a tour or visitors' programme. This contribution explains how Iscor, and more specifically its Mining Department, attempts to reach its objectives in this regard.